THE FUNCTION OF MEMORY AND HISTORY IN POSTCOLONIAL LITERATURE - Ne`matova Dilshoda Xurmatillo qizi; Abdurakhmanova Diana Valerevna (TADQIQOTLAR.UZ, 2024)
Abstract: This article explores how postcolonial writers use memory to resist colonial  erasures  and  affirm  cultural  heritage,  while  also  addressing  the  lasting psychological  and  societal  impacts  of  colonial  rule.  By  examining  works  such  as Things Fall Apart by Chinua Achebe, Midnight’s Children by Salman Rushdie, and Wide  Sargasso  Sea  by  Jean  Rhys,  the  essay  highlights  how  memory  and  history intersect to challenge dominant colonial narratives and assert alternative perspectives. It further discusses the intergenerational transmission of memory and its role in shaping collective identities, as well as the potential for memory to facilitate reconciliation and healing  in  postcolonial  societies.  Ultimately,  memory  and  history  emerge  as indispensable  elements  in  postcolonial  literature,  offering  pathways  for  resistance, understanding, and renewal in the aftermath of colonization.